Pengaruh Kepemimpinan terhadap Motivasi dan Kinerja Karyawan serta Implikasinya terhadap Kepuasan Kerja (Studi pada Bank Pembangunan Daerah (BPD) Sulawesi Tenggara) - Supendy, Rustam (Universitas Brawijaya, Indonesia, 2012)
This reaserch is empirically aimed at testing and proving the effect of leadership model towardmotivation and the workers’performance and implication toward the direct and indirect work satisfaction.Leadership, as the main variable on this study, is classified into two variables those are the TransformationalLeadership Model and the Transactional Leadership Model. The Objective of this research is toanalyze and to test the effect of (1) the transformational leadership model toward the workers’motivation;(2) the transactional leadership model toward the workers’motivation; (3) the transformational leadershipmodel toward the workers’performance; (4) thde transactional leadership model toward the workers’performance; (5) the workers motivation toward their performance; and (6) the workers’performancetoward their motivation. Hopefully, this study willl enrich the knowladge about managemant, especiallythe development of human resource managemant which is related to leadership and organization behavior.Moreover, it will give benefit for both the scholars and the practitioners. The population of this study is allpermanent workers of Bank Pembangunan Daerah of South-East Sulawesi with the total number of 385people. There are 196 people used as the sample which is taken by using Slovin formula. The Sample istaken by using proportional random sampling. The analysis method used is the Structural Equation Medeling(SEM). The AMOS 18.00 software is also applied. The findings of the study show that: 1) the variable oftransactional leadership model is the dominant leadership model wichh increase workers; motivation,performance, and satisfaction; 2) the transformational leadership model cannot direcly increase the workers’performance without motivating the workers; 3) the transactional leadership model cannot direclyincrease the workers’performance without motivating the workers.